Reducing mass-transport limitations in cobalt-electrolyte-based dye-sensitized solar cells by photoanode modification - Mhaisalkar, Subodh Gautam (2014)
Mass transport has been identified as a limiting problem in the photovoltaic performance of dye-sensitized solar cells based on electrolytes consisting of ionic liquids or cobalt complexes. A mixed TiO2 macroporous–mesoporous morphology employed as photoanode is demonstrated to assist the diffusion of electrolytes with higher viscosity or consisting of bulky redox mediators, such as cobalt di-tert-butyl bipyridine [Co(dtb)3]2+/3+. This morphology with large pores improves the non-linearity of photocurrent response to light intensity indicating better diffusion. The incorporated sub-micrometer pores also reduce recombination and decrease diffusion resistance, as revealed by electrochemical impedance spectroscopy.